Effect of Ethephon, Boron and Zinc Spray on Anatomical Characters of Sunflower Crop (Helianthus annuus L.) - A, Makkiyah; Kadhum, Fawzi; Attiya, Hatim (Iraqi Journal of Science, 2024)
The experiment field was carried out during spring season of 2006 on experimental farm of Field Crop Science Department College of Agriculture, University of Baghdad, to study the effect of foliar applications of Ethephon, Boron and Zinc on the number of vascular bundles in stem and some characteristics of xylem- in sunflower hybrid (ZahratilIraq).By using the Randomized Complete Block Design with three replications. Eight treatment were used: control treatment (with water spray only), Ethephon (0.480 kg.a.i/ha), Boron (200 g/L), Zinc (50 mg/L) and the interaction between them. The results revealed significant anatomical changes in disc peduncles of plants caused by the foliar applications of Ethephon, Boron, and Zinc treatments. Boron and Zinc increased the total number of vascular bundles and xylem vessels rows compared with control.However (Boron+Zinc) treatment caused higher increment in number of vascular bundle, xylem rows and their vessels. It is assumed that this results should be find their effects, some how positively, on growth, development and yield of sunflower crop.